SIMULASI SKEMA UNIVERSAL FILTERED MULTI-CARRIER (UFMC) PADA SISTEM KOMUNIKASI DIGITAL - Fauzan, Rafi Ardhan; Wellem, Theophilus (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Universal Filtered Multi-Carrier (UFMC) is a multi-carrier modulation scheme that is an alternative to the Orthogonal Frequency Division Multiplexing (OFDM) scheme currently used in 4G communication systems and wireless local area networks (WLAN). The weakness of OFDM lies in the high peak-to-average power ratio (PAPR) value and out-of-band (OOB) emission which can cause interference between carriers. UFMC is one of the schemes used to overcome the weaknesses of OFDM. This research aims to study the performance of UFMC for data transmission on AWGN channel with 256-QAM, 1024-QAM, and 4096-QAM modulation. In addition, 256-point, 512-point, and 1024-point FFTs were also used to see the effect on the achievable bit error rate (BER) and PAPR value. The simulation results show that for all simulated FFT sizes and QAM values, 256-QAM produces the lowest BER value. Using a 1024-point FFT, a BER of 10-3 can be achieved with an SNR of 20 dB. The lowest PAPR value obtained in the simulation is 7.1891 dB.